Reconstructive Lymph Vascular Surgery - Baumeister, Ruediger G.H (Springer International Publishing : Imprint: Springer, 2017)
This book represents an up-to-date overview of reconstructive lymph vascular surgery, with coverage of all aspects from the bench to the bedside. After careful consideration of the pathophysiological and experimental basis for the described procedures, concise guidance is provided in the treatment of various conditions with a view to facilitating and refining microsurgical training. Surgical technique is explained for the important indication of lymphedema of the upper and lower limbs due to localized blockage of the lymphatic system, which may be either primary or secondary, e.g., the result of lymph node resection or trauma. Further important indications for which the surgical procedure is fully described include lymphoceles and lymph fistulas. Means of verifying results, especially important in the case of newer techniques, are discussed and the results obtained with the different techniques are extensively documented. Owing to the delicate structure of the vessels, the lymph vascular system is the last part of the vascular system to be treated with vascular surgical methods using end-to-end and end-to-side anastomoses and bypass procedures. Reconstructive Lymph Vascular Surgery will be an informative and instructive guide to current possibilities of reconstructive lymph vascular surgery and for interested readers in the fields of angiology, dermatology, gynecology, oncology, phlebology, physiotherapy, and surgery.